Salubong an immersive cultural + spiritual landscape and academic hub - Sagcal, Janelle Paola R. (College of Architecture, University of the Philippines Diliman, 2020)
In every emerging city, preserving the cultural heritage and facility modernization are two concepts that are always brought head-to-head and regarded to belong on the opposite ends of the architectural spectrum. This comes with the reason that most Philippine modern cities are exchanging small-town culture and traditional and cultural city elements with concrete roads and jungles draped in glass and steel. Almost like these cities, Antipolo is slowly inching its way on the brink of aggressive urban development. Factors like urban sprawl, the proliferation of central business districts, and the pressure to deliver and compete with modern cities threaten the city's heritage and cultural roots as well as its natural reserves. This design project proposes that development does not have to come with a price -- especially on a city that thrives on its cultural heritage and environmental features. This is exhibited in SALUBONG : an immersive cultural landscape and academic hub. Aiming to address the lack of in-city facilities and to manage and accommodate the growing population, SALUBONG envisions architecture that adapts, empowers its users, and revitalized the city's cultural and spiritual identity rather than losing it.